Synthesis and Antiproliferative Activity of Steroidal Thiosemicarbazone Platinum (Pt(II)) Complexes. (8th October 2015) - Huang, Yanmin; Kong, Erbin; Gan, Chunfang; Liu, Zhiping; Lin, Qifu; Cui, Jianguo
Abstract : Steroidal compounds exhibit particular physiological activities. In this paper, some steroidal thiosemicarbazones platinum (Pt(II)) complexes were synthesized by the condensation of steroidal ketones with thiosemicarbazide using estrone, chenodeoxycholic acid, and 7-deoxycholic acid as starting materials and complexation of steroidal thiosesemicarbazones with Pt(II). The complexes were characterized by IR, NMR, and MS, and their antiproliferative activities were evaluated. The results showed that some steroidal thiosemicarbazones platinum (Pt(II)) complexes displayed moderate cytotoxicity to HeLa and Bel-7404 cells. Thereinto, complex6 showed an excellent inhibited selectivity to HeLa cells with an IC50 value of 9.2  μ M and SI value of 21.7. At the same time, all compounds were almost inactive to HEK293T (normal kidney epithelial cells). The information obtained from the studies may be useful for the design of novel chemotherapeutic drugs.